Preliminary Study on the Synthesis of Phosphorylated Mung Bean Starch: The Effect of pH on the Physicochemical and Functional Properties - Illona Nathania; Asaf Kleopas Sugih; Henky Muljana (Universitas Gadjah Mada, 2017)
Mung bean (Vigna radiate L.) is a grain legume widely cultivated in tropical and sub-tropical regions. Mung bean seeds contain a significant amount of carbohydrate (63%-w/w) and are easily digested compared to seeds from other legumes. Mung bean starch has the potential to be used as thickener or gelling agents in food industries. Certain functional properties of mung bean starch, however, still need to be improved. In this research, a preliminary study was performed to upgrade mung bean starch properties using phosphorylation reaction. In particular, the effect of starch suspension pH (6–10) on the functional properties of the modified products was investigated. Phosphorylation was carried out at 130 °C, for 2 h using sodium tripolyphosphate (STPP) with an intake of 5%-w based on dry starch. The phosphorylated products were subsequently washed with water and dried. The experimental results show that the P-content of the phosphorylated mung bean starch is accessible in the range of 0.04–0.08%. The solubility (6.09–11.37%-w/w) and swelling power (9.88–11.17 g/g) of the modified starch products have been improved compared to native starch (solubility = 6.06 %-w/w, swelling power = 8.05 g/g). Phosphorylation also proved to increase peak viscosity, paste clarity, and water absorption/oil absorption capacity of the products.